Effect of whey protein concentrate and sodium chloride addition plus tumbling procedures on technological parameters, physical properties and visual appearance of sous vide cooked beef - Szerman, Natalia; Gonzalez, Claudia Beatriz; Sancho, Ana Maria; Grigioni, Gabriela Maria; Carduza, Fernando Jose; Vaudagna, Sergio Ramon (2019)
Beef muscles cooked by the sous vide system were evaluated for the effects of pre-injection tumbling, brine addition and post-injection tumbling on technological parameters, physical properties, visual appearance and tissue microstructure. The muscles were injected at 120% (over original weight) with a brine formulated to give a concentration of 3.5% whey protein concentrate and 0.7% sodium chloride on an injected raw product basis. Pre-injection tumbling did not affect most of the evaluated parameters. Brine addition reduced significantly the cooking and total weight losses. Total weight loss was 7.2% for injected muscles, and significantly higher (28.2%) for non-injected ones. Brine incorporation increased pH and reduced shear force values of cooked muscles. Extended post-injection tumbling (5 rpm–10 h) improved brine distribution and visual appearance, and also diminished the shear force values of cooked muscles. However, this treatment increased the weight losses of post-injection tumbling and cooking-pasteurization stages.